THE EFFECT OF ORGANIZATIONAL CULTURE, JOB STRESS, WORK-LIFE BALANCE AND MOTIVATION ON JOB SATISFACTION (Case Study: Human Resources in Indonesia’s Animation Industry) - Charvia Liesera; Bernadetta Dwi Suatmi (Bajang Institute, 2024)
The animation industry in Indonesia is a developing industry, with several problems that are inevitable, such as the lack of human resources by quality and quantity to suffice the needs of the industry. Animation, as one of service industry that depends a lot on human resources for production, requires adequate human resources who can carry out maximum effort to reach the organizational needs. One of the aspects to fulfil these needs is by increasing job satisfaction, in hope that it could improve productivity and work quality. This research aims to analyse the relationship between organizational culture, job stress, work-life balance and motivation towards job satisfaction amongst human resources in Indonesia’s animation industry. Data collection is done by sharing out questionnaire, and is processed with multiple linear regression analysis using SPSS program. Analysis findings based on 268 respondents found that organizational culture has a positive and significant impact towards job satisfaction, job stress has a negative and significant impact towards job satisfaction, work-life balance has a positive and significant impact towards job satisfaction, and motivation has a positive and significant impact towards job satisfaction